2009
DOI: 10.1016/j.jacc.2009.08.030
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Reduces Systemic Blood Pressure and Improves Early Markers of Atherosclerosis in Pre-Pubertal Obese Children

Abstract: A regular physical activity program reduces BP, arterial stiffness, and abdominal fat; increases cardiorespiratory fitness; and delays arterial wall remodeling in pre-pubertal obese children. (Effects of Aerobic Exercise Training on Arterial Function and Insulin Resistance Syndrome in Obese Children: A Randomized Controlled Trial; NCT00801645).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
413
6
27

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 360 publications
(471 citation statements)
references
References 52 publications
25
413
6
27
Order By: Relevance
“…However, regular physical activity results in a significant reduction of BP, not only when measured in the office, but also when monitored for 24-h BP. After 3 months of exercise training the effects on BP were 7-12 mmHg for SBP and 2-7 mmHg for DBP (198). Higher levels of physical activity were associated with lower BP and results suggested that the volume of activity might be more important than the intensity (199).…”
Section: Blood Pressure Target In Diabetic and Renal Diseasementioning
confidence: 94%
“…However, regular physical activity results in a significant reduction of BP, not only when measured in the office, but also when monitored for 24-h BP. After 3 months of exercise training the effects on BP were 7-12 mmHg for SBP and 2-7 mmHg for DBP (198). Higher levels of physical activity were associated with lower BP and results suggested that the volume of activity might be more important than the intensity (199).…”
Section: Blood Pressure Target In Diabetic and Renal Diseasementioning
confidence: 94%
“…6,7 There is evidence that levels of physical activity, aerobic fitness and CVD risk factors track from childhood and adolescence into adulthood. 8 A number of observational studies have investigated associations between physical activity and BP in children and adolescents, [9][10][11][12] but the findings from these studies have been equivocal. Recently, a UK study of 5505 children aged 11-12 years showed that higher levels of physical activity were associated with lower BP, and the authors concluded that the volume of activity may be more important than the intensity.…”
Section: Introductionmentioning
confidence: 99%
“…More important, this study ruled out key variables and potential confounders that could affect blood pressure. Weight loss, loss of adiposity, and increases in activity are known to have positive effects on blood pressure profiles 35, 36, 37, 38, 39. However, the experimental paradigm used in the current study uses obese mice that share similar metabolic profiles in that body mass, total fat content, oxygen consumption, and activity levels remain unchanged with or without increased muscle mass.…”
Section: Discussionmentioning
confidence: 99%